Dermoscopic features of acral melanocytic nevi in a case series from Mexico - González Ramírez, Roger Adrián; Guerra Segovia, Carolina; Garza Rodríguez, Verónica; Garza Báez, Pamela; Gómez Flores, Minerva; Ocampo Candiani, Jorge (Sociedade Brasileira de Dermatologia e Sifilografia, 2018)
Background: Pigmented lesions on acral sites are common; clinical differentiation of nevi and early melanoma can be challenging. In these cases, dermoscopy can provide a more accurate diagnosis. Most dermoscopic patterns on acral skin have been described in Asian and European populations, while there are few studies in Latin American populations.